Nastanek in razvoj ruralnega socialističnega podjetja - Piškurić, Jelka (Časopis za zgodovino in narodopisje, 2025)
In this article, the author examines the development of the Ig Metal Industry during the socialist period. Through the example of this local enterprise, she highlights key characteristics of socialist rural development and emphasizes that socialism was a social system grounded in the ideology of industrial modernization. The company was established as part of the second phase of nationalization, through which the state in 1948 introduced new economic relations in almost all non-agricultural sectors; this measure had not only economic but also political motives. The Ig Metal Industry, which the authorities of the time regarded as an enterprise of district-level importance, gradually expanded from modest beginnings and by the end of the period under review began producing a wide range of products. It became the largest employer in the locality, but its significance extended beyond economic development, as it also played an active role in other areas of the community’s social life.
Keywords: :socialism; 1948–1990; economic development; gospodarski razvoj; Ig Metal Industry; industrialization; Kovinska industrija Ig; nacionalizacija; nationalization; ndustrializacija; podeželje; rural areas; socializem